2021
DOI: 10.12965/jer.2142154.077
|View full text |Cite
|
Sign up to set email alerts
|

Relations between postural sway and cognitive workload during various gaze tasks in healthy young and old people

Abstract: The purpose of this study was to determine whether postural control would differ under various gaze tasks while standing in a wide or narrow stance between healthy young and old people, and also investigate whether postural sway and cognitive workload are affected by dualtask balance. Ten young and 10 healthy old people participated in this study. Each participant stood upright under four gaze conditions (fixation, saccade, pursuit, vestibular-ocular reflex) and two stance conditions (wide and narrow stance) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Body sway was attenuated when rectilinear and uniformly moving visual targets were presented during BP standing on a normal platform (an easy postural control task) [ 13 ]. By contrast, there was greater postural sway when similar visual targets were presented during a narrow stance and standing on a force plate covered with a foam cushion (difficult postural task) [ 17 , 18 ]. To verify these hypotheses, several patterns of moving visual targets were presented to the participants under BP and UP standing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Body sway was attenuated when rectilinear and uniformly moving visual targets were presented during BP standing on a normal platform (an easy postural control task) [ 13 ]. By contrast, there was greater postural sway when similar visual targets were presented during a narrow stance and standing on a force plate covered with a foam cushion (difficult postural task) [ 17 , 18 ]. To verify these hypotheses, several patterns of moving visual targets were presented to the participants under BP and UP standing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…These directions contain information that are necessary in understanding the behavioural patterns inherent to the sensory systems. Most studies have utilised these directions in conducting postural sway analysis Roh et al (2021). investigated the differences in postural control between healthy young and old people under various four gaze tasks (fixation, saccade, pursuit, and vestibular-ocular reflex) using their COP mean sway amplitude in the ML and AP directions.…”
mentioning
confidence: 99%
“…investigated the differences in postural control between healthy young and old people under various four gaze tasks (fixation, saccade, pursuit, and vestibular-ocular reflex) using their COP mean sway amplitude in the ML and AP directions. The result suggested that postural sway significantly reduces with saccade eye movement for both young and old while the vestibularocular reflex results in greater postural sway(Roh et al, 2021). Similarly, Shafizadeh et al(2020) investigated the effect of age and task difficulty on postural sway, variability and complexity among children, young adults and older adults using their respective COP sway displacement in the ML and AP directions.…”
mentioning
confidence: 99%